The Effect Of Multi-Year Sports Training On The Functional Status Of The Cardiovascular System Of Athletes - Turumbetov Usman Yusupbaevich (Zien Journals, 2024)
The effect of long-term sports training on the functional state of the cardiovascular system of young athletes and the mechanisms controlling the body's adaptation to various physical loads and stress factors during sports training are given.
Keywords: Heart; cardiovascular system; functional state